Ownership and the donor-recipient relationship - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2009)
At the centre of the Paris Declaration on Aid Effectiveness is the idea of country ownership. It is meant to change the situation in many aid dependent African countries where donors dominate decision-making over which policies are adopted, how aid is spent, and what conditions are attached to its release. This article assesses the impact of recent aid reforms to put ownership into practice.
Keywords: 330; Entwicklungshilfe; Internationale Wirtschaftsbeziehungen; Souveränität; Afrika